Money market integration - Leonardo Bartolini; Spence Hilton; Alessandro Prati (Federal Reserve Bank of New York, 2005)
We use transaction-level data and detailed modeling of the high-frequency behavior of federal funds-Eurodollar yield spreads to provide evidence of strong integration between the federal funds and Eurodollar markets, the two core components of the dollar money market. Our results contrast with previous research indicating that these two markets are segmented, showing them to be well integrated even at high (intraday) frequency. We document several patterns in the behavior of federal funds-Eurodollar spreads, including liquidity effects from trading volume on yield spreads' volatility. Our analysis supports the view that targeting federal funds rates alone is sufficient to stabilize rates in the (much larger) dollar money market as a whole.
Keywords: E43; E44; E52; 330; federal funds; Eurodollar; market segmentation; Geldmarkt; Euromarkt; Marktintegration; Marktsegmentierung; USA